Methods for incorporating population dynamics and decision theory in cackling goose management - Williams, Perry J., author; Kendall, William L., advisor; Hooten, Mevin B., committee member; Schmutz, Joel A., committee member; Wei, Yu, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.